Pengaruh Impor dan Tarif Bea Masuk terhadap Pertumbuhan Pasar Skincare Korea di Indonesia Periode 2020–2023 - Octaviane, Devi; Maharani Rahma (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The Korean skincare market in Indonesia experienced rapid growth during the 2020–2023 period, driven by the global K-beauty trend, increasing consumer demand, and the expansion of e-commerce distribution channels. However, the influence of import value and import duty rates on market growth still requires empirical examination. This study aims to quantitatively analyze the impact of imports and import duties on the growth of the Korean skincare market in Indonesia. Secondary data were obtained from Statistics Indonesia, the Directorate General of Customs and Excise, and UN Comtrade, and analyzed using multiple linear regression to test both partial and simultaneous effects of the independent variables on the dependent variable. The results reveal that import value has a positive and significant effect on market growth, while import duties show no significant influence. These findings confirm that imports are the dominant factor driving market expansion. In conclusion, import management strategies are essential for developing the Korean skincare market in Indonesia and provide a basis for businesses and policymakers to design sustainable trade strategies.